2022
DOI: 10.1002/lio2.830
|View full text |Cite
|
Sign up to set email alerts
|

Virtual planning and 3D‐printed guides for mandibular reconstruction: Factors impacting accuracy

Abstract: Objectives: Examine accuracy and factors impacting accuracy for mandibular reconstruction with virtual surgical planning, 3D printed osteotomy guides and preoperatively bent mandibular reconstruction plate (VSP/3Dprinted-guide/plate). Method: Retrospective review of osseous-free-flap mandibular reconstructions with VSP/3Dprinted-guide/plate between January 2015 and July 2020 at a single academic medical center. Patient demographics, disease, and treatment variables were extracted. Accuracy was assessed by 3D-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Participants were predominantly male (n = 10 [59%]) and non-Hispanic White (n = 14 [82%]), consistent with our center’s practice and similar populations nationally . The most common free flap type was fibular (n = 8 [47%]), a higher proportion than national data due to practice patterns at our center …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Participants were predominantly male (n = 10 [59%]) and non-Hispanic White (n = 14 [82%]), consistent with our center’s practice and similar populations nationally . The most common free flap type was fibular (n = 8 [47%]), a higher proportion than national data due to practice patterns at our center …”
Section: Resultsmentioning
confidence: 91%
“…23,24 The most common free flap type was fibular (n = 8 [47%]), a higher proportion than national data due to practice patterns at our center. 23,25 Thematic Analysis Three distinct themes were identified: (1) the tremendous effect of preoperative counseling on surgical decision-making and satisfaction; (2) coexisting and often conflicting priorities regarding survival vs quality of life; and (3) surgery as a momentous and distressing event (Figure).…”
Section: Key Pointsmentioning
confidence: 99%
“…In the literature, several CAS approaches were presented in the field of mandibular reconstruction, with a variety of implementations and different reported deviations, ranging from 0-12.5 mm for displacements and 0.9-17.5 • for angles [30]. One approach of Virtual Planning Surgery (VPS) with a 3D printed guide showed deviations between 1.76-3.11 mm, with a decreased accuracy for long donor bone segments [31]. Other mandibular VPS accuracy studies, on a smaller numbers of patients, reported deviations of 2.00 mm and 1.30 mm for mandibular and fibular osteotomies [32], 0.2-2.7 mm [33], 2.06 mm [34], and 0.9-1.3 mm for fibular size [35], 1.8 mm for resection planes and 3.0 mm and 4.2 • for fibular length and angulation [36], 3.06-3.76 mm and 8.5-10.4 • for resection planes [37], and of 2.92-5.61 mm and 3.85-5.88 • for spatial and angular cutting plane deviations [38].…”
Section: Discussionmentioning
confidence: 99%
“…These transplants have several advantages, including high success rates, minimal donor-site morbidity, and excellent functional and aesthetic outcomes. The successful implementation of these methods is supported by several devices and tools, such as microsurgical instruments, tissue expanders, and Computer-Aided Design and Manufacturing (CAD/CAM) systems for planning and performing the mandible reconstruction (Annino Jr. et al 2022;Barr et al 2020).…”
Section: Introductionmentioning
confidence: 99%